2023
DOI: 10.3390/met13020410
|View full text |Cite
|
Sign up to set email alerts
|

A Tribological Investigation of the Titanium Oxide and Calcium Phosphate Coating Electrochemical Deposited on Titanium

Abstract: Titanium (Ti) and its alloys are widely used in biomedical applications due to their excellent mechanical properties and biocompatibility. However, they are a concern due to the possibility of cytotoxic effects coming from the degradation products. This degradation occurs by the combined action of corrosion and mechanical wear of these materials, which are released in the biological environment by the biomaterial implanted. The present article aims to investigate a new route to improve electrochemical and trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The addition of TiO 2 can stabilize the phosphate lattice of calcium phosphate materials. It has been reported that TiO 2 can improve chemical stability and module of elasticity and increase the viscosity of calcium phosphate systems. …”
Section: Introductionmentioning
confidence: 99%
“…The addition of TiO 2 can stabilize the phosphate lattice of calcium phosphate materials. It has been reported that TiO 2 can improve chemical stability and module of elasticity and increase the viscosity of calcium phosphate systems. …”
Section: Introductionmentioning
confidence: 99%